The cost of routine operative cholangiography - Delgado, Bolivar (Cirugía del Uruguay, 1986)
Analysis of !he cost and cost/effectiveness of routine operative cholangiography chiefly with reference to the diagnosis of choledocian lithiasis, decrease in the mortality rate in surgery of biliary lithiasis and decrease in the number of unnecesary choledoctomies. The results of the author's personal series of 656 cholecystetomies for lithiasis with routine operative cholangiography are compared with results thal statistically could have been expected íf this diagnostic technique had not been employed in said series choledoctomy based on classical índicatíons had been effected.